Molecular Markers and Conservation of Plant Species in the Latin-America: The Case of Phaedranassa viridiflora (Amaryllidaceae) - Oleas, Nora (2013)
Phaedranassa viridiflora (Amaryllidaceae) is an endemic and endangered plant restricted to the Northern Andes in Ecuador. It is known in three locations where it is sympatric with other Phaedranassa species. Phaedranassa viridiflora is the only species of the genus with yellow flowers. We analyzed 13 microsatellite loci to elucidate the genetic structure of the populations of P. viridiflora. Our results provided the first evidence of natural hybridization in the genus (between P. viridiflora and P. dubia in the Pululahua crater of northern Ecuador). The central and southern populations did not show hybridization. Genetic diversity was the highest in the Pululahua population. Central and southern populations have a higher proportion of clones than Pululahua. Bayesian and cluster analysis suggest that the yellow flower type evolved at least three times along the Ecuadorean Andes. In contrast to other Phaedranassa species, Phaedranassa viridiflora shows lower genetic diversity, which is likely related to a vegetative reproductive strategy. © 2013 The New York Botanical Garden (outside the USA).